Construction Dispute Resolution: Alternative Construction Dispute Resolution, Mediation, and Arbitration - Taufik Hidayat; Sami’an Sami’an (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Construction dispute resolution in Indonesia often faces challenges, such as lengthy processes and high litigation costs in court proceedings. Therefore, alternative dispute resolution methods, such as mediation and arbitration, have become appealing solutions. This study aims to analyze the effectiveness of resolving construction disputes through mediation and arbitration using a normative juridical method. The approach includes the analysis of legislation, legal doctrines, and relevant case studies. The results show that mediation offers advantages such as a fast process, low cost, and the preservation of good relationships between parties. However, mediation outcomes are non-binding, making their effectiveness dependent on the willingness of parties to adhere to agreements. On the other hand, arbitration provides final and binding decisions with executive power, making it more suitable for complex and high-value disputes. Nevertheless, arbitration's relatively high costs and ambiguities in arbitration clauses within contracts often hinder its implementation. This study also identifies the need for further education for construction actors regarding the benefits of alternative dispute resolution (ADR) mechanisms, strengthening the role of institutions such as the Indonesian National Arbitration Board (BANI), and drafting clearer arbitration clauses in construction contracts. With regulatory enhancements and increased awareness, mediation and arbitration can become more effective and efficient alternatives for resolving construction disputes in Indonesia.